Comparison between Electromotive Force and Electric Potential Difference (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The aim of this review is to compare electromotive force and electric potential and to find out similarities and some major differences between them. We found that emf is a complex concept for elementary physics’ students and has serious problems in its understanding, while the concept of Pds is relatively easy. EMF keeps potential difference while potential difference causes current to flow. Moreover, some major differences between emf and electrical potential are highlighted like EMF is cause and potential difference is effect, Electromotive force is the amount of energy that is given to one coulomb of charge to go around whole circuit while Potential difference is the amount of energy used by one coulomb of charge. That is why they are not synonyms words. Teachers and students should be careful in their usage. Because of the name, some people think electromotive force as a force, actually it is not a force but it is the energy that is used to maintain a constant potential difference between two points. Emf shows how much energy is supplied to the circuit to move one coulomb of charge across the whole circuit. Emf is greater than the potential difference between any two points. Potential difference is always less than the maximum value of emf when the battery is fully charged. Although electromotive force and potential difference has some similarities like they have same SI unit(volt) and their dimension is same , potential difference is the key to how current flows, but there are many differences that I have highlighted in this article.